Geistige Gefahr und Immunisierung der Gesellschaft. Antikommunismus und politische Kultur in der frühen Bundesrepublik - Creuzberger, Stefan 1961- (Schriftenreihe der Vierteljahrshefte für Zeitgeschichte Sondernummer, 2014)
Up to the early 1960s, anticommunism was an important source of identity formation in the Bonn Republic. It aimed at consolidating the still-nascent West German democracy. Renowned historians discuss different governmental and social forms of anticommunism in the pan-German context